VENOUS THROMBOEMBOLISM WITH THE USE OF ASPIRIN VERSUS ENOXAPARIN AS PROPHYLACTIC AGENTS AFTER HIP ARTHROPLASTY - Bukhari, Syed Imran; Muhammad Basir Khan; Asif Zahir; Sajjad Alam; Farhad Ullah (Journal of Postgraduate Medical Institute, 2023)
Objective: To assess how often venous thromboembolism (VTE) occurs in patients on low dosage aspirin versus enoxaparin for VTE prevention after hip arthroplasty. Methodology: This quasi-randomized controlled trial was conducted at the Department of Trauma & Orthopedics, Lady Reading Hospital, Peshawar. The study was conducted over a period of 6 months. Lottery method was used to collect data and the patients were divided into two groups. The chi-square test was used to compare the frequency of VTE between groups. Effect modifiers such as age, gender, and BMI were managed through stratification. The post-stratification chi-square test was used to determine whether there is a relationship between these impact modifiers and study results. P-value 0.05 was used to define a significant difference. Results: A total of 74 patients undergoing total/partial hip arthroplasty in orthopedics surgery were observed, which were divided in two equal groups. Patients in Group A were managed by aspirin (75mg/day) and Group B patients received enoxaparin (0.5mg/kg). Group A had 2(5.4%) patients with VTE in follow-up and 35(94.6%) patients had observed no VTE. Group B had VTE in 4(10.8%) patients and no VTE in 33(89.2%) patients which shows that VTE was high in group B as compared to group A. The difference was insignificant with p-value=0 .337. Incidence of VTE was seen to be higher in patients aged more than 50 years. Conclusion: The difference in incidence of VTE after hip arthroplasty with use of either Aspirin or Enoxaparin as prophylactic agents was statistically insignificant.